Skip to main content
Physics LibreTexts

10.3: C- Clinic on the Gamma Function

  • Page ID
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)\(\newcommand{\AA}{\unicode[.8,0]{x212B}}\)

    The gamma function Γ(s) is defined, for s > 0, by

    \[ \Gamma(s)=\int_{0}^{\infty} x^{s-1} e^{-x} d x.\]

    Upon seeing any integral, your first thought is to evaluate it. Stay calm. . . first make sure that the integral exists. A quick check shows that the integral above converges when s > 0.

    There is no simple formula for the gamma function for arbitrary s. But for s = 1,

    \[ \Gamma(1)=\int_{0}^{\infty} e^{-x} d x=-\left.e^{-x}\right|_{0} ^{\infty}=1.\]

    For s > 1 we may integrate by parts,

    \[ \int_{0}^{\infty} x^{s-1} e^{-x} d x=-x^{s-1}\left.e^{-x}\right|_{0} ^{\infty}+(s-1) \int_{0}^{\infty} x^{s-2} e^{-x} d x,\]


    \[ \Gamma(s)=(s-1) \Gamma(s-1) \quad \text { for } s>1.\]

    Apply equation (C.4) repeatedly for n a positive integer,

    \[ \Gamma(n)=(n-1) \Gamma(n-1)=(n-1)(n-2) \Gamma(n-2)=(n-1)(n-2) \cdots 2 \cdot 1 \cdot \Gamma(1)=(n-1) !,\]

    to find a relation between the gamma function and the factorial function. Thus the gamma function generalizes the factorial function to non-integer values, and can be used to define the factorial function through

    \[ x !=\Gamma(x+1) \quad \text { for any } x>-1.\]

    In particular,

    \[ 0 !=\Gamma(1)=1.\]

    (It is a deep and non-obvious result that the gamma function is in fact the simplest generalization of the factorial function.)

    The gamma function can be simplified for half-integral arguments. For example

    \[ \Gamma\left(\frac{1}{2}\right)=\int_{0}^{\infty} x^{-1 / 2} e^{-x} d x=\int_{0}^{\infty} y^{-1} e^{-y^{2}}(2 y d y)=\int_{-\infty}^{\infty} e^{-y^{2}} d y=\sqrt{\pi}\]

    where we used the substitution \(y=\sqrt{x}\). Thus

    \[ \Gamma\left(\frac{3}{2}\right)=\frac{1}{2} \Gamma\left(\frac{1}{2}\right)=\frac{\sqrt{\pi}}{2}=\left(\frac{1}{2}\right) !,\]

    \[ \Gamma\left(\frac{5}{2}\right)=\frac{3}{2} \Gamma\left(\frac{3}{2}\right)=\frac{3}{4} \sqrt{\pi},\]

    and so forth.

    This page titled 10.3: C- Clinic on the Gamma Function is shared under a CC BY-SA license and was authored, remixed, and/or curated by Daniel F. Styer.

    • Was this article helpful?